RESPON PERTUMBUHAN DAN HASIL ROSELLA DENGAN PEMBERIAN KOMBINASI POC BIOSAKA DAN KNO3 PADA TANAH GAMBUT - Saputri, Gita; Zulfita, Dwi; Pramulya , Muhammad (Fakultas Pertanian Universitas Janabadra, 2025)
The rosella plant (Hibiscus sabdariffa L.) is a shrub or shrub which is a seasonal plant. This research aims to obtain the best combination of Biosaka POC concentration and KNO3 fertilizer dose for growth and yield of rosella in peat soil. This research was carried out at Sepakat 2, Gang Racana Untan, Pontianak, starting in February - May 2024. This research used a Completely Randomized Design (CRD) consisting of five treatments and five replications, each replication consisting of four plant samples. The treatment in question is 100% Biosaka POC equivalent to 300 ml/liter (k1), 75% Biosaka POC equivalent to 225 ml/liter + 25% KNO3 (100 kg/ha) equivalent to 0.5 g/plant (k2), 50% POC Biosaka equivalent to 150 ml/liter + 50% KNO3 (200 kg/ha) equivalent to 1 g/plant (k3), 25% POC Biosaka equivalent to 75 ml/liter + 75% KNO3 (300 kg/ha) equivalent to 1.5 g/plant (k4), 100% KNO3 (400 kg/ha) equivalent to 10 g /plant (k5). The results of the research show that giving 100% KNO3 can provide the best growth, namely plant height and the combination of 25% Biosaka and 75% KNO3 can provide the best rosella yields on peat soil.